Tripartite Motif 22 and Class II Transactivator Restriction Factors: Unveiling Their Concerted Action against Retroviruses - Forlani, Greta; Accolla, Roberto S. (Frontiers in Immunology, 2017)
Coevolution of the three basic mechanisms of immunity, intrinsic, innate and adaptive, is a constant feature of the host defense against pathogens. Within this frame, a peculiar role is played by restriction factors, elements of intrinsic immunity that interfere with viral life cycle. Often considered as molecules whose specific functions are distinct and unrelated among themselves recent results indicate instead, at least for some of them, a concerted action against the pathogen. Here we review recent findings on the antiviral activity of TRIM22 and CIITA, firstly discovered as HIV-1 restriction factors, but endowed with general antiviral activity. TRIM22 and CIITA provide the first example of cellular proteins acting together to potentiate their intrinsic immunity.